The correlation between CYP2C19 Polymorphisms and recurrent risk in Patients with Ischemic Stroke treated with Clopidogrel in Kurdistan region-Iraq - Hind Salim Jardaq; Mohammed Y. Jamal (College of Pharmacy University of Baghdad, 2022)
Clopidogrel is a prodrug that must be transformed into an active metabolite by hepatic cytochrome P450 (CYP) isoenzymes to prevent platelet clotting. Polymorphisms of the CYP2C19 gene can cause a reduction or complete loss of CYP2C19 enzyme activity resulting in inhibiting clopidogrel metabolism, effectiveness and increase stroke recurrence risk in ischemic stroke patients. This study aims to investigate the correlation between genetic polymorphisms in CYP2C19*2 and*3 and recurrent risk in patients with ischemic stroke taking clopidogrel 75mg in Kurdistan region -Iraq. This retrospective case-control study was carried out at Kurdistan, Erbil, Medicina medical center, and Rizgary general hospital from January 2021 to August 2021. The blood sample was taken from the participants and tested for genotyping. The collection of data was taken from patients' medical charts in the hospital and patients' electronic medical records from the neurology clinic.  Sixty patients participated, (34) were male and (26) were female, with age range (38-96) years, diagnosed from not more than two years with ischemic stroke and taking 75 mg clopidogrel maintenance dose. Genotyping analysis showed 61.7 % were homozygotes for wild allele *1, the heterozygotes divided into 26.7% (*1/*2) and 6.7 % (*1/*3) genotype, while the homozygotes for mutant alleles CYP2C19*2,*3 distributed in 3.3 %(*2/*2) and 1.7 %(*3/*3). The (*2/*3) was not detected in the study population. A significant relation was found between risk of stroke recurrence with carrying the variant allele CYP2C19 *2, reduced CYP2C19 enzyme metabolic activity, and ACEIs/ARBs usage (P = 0.024, P = 0.039, P=0.24 respectively). On the other hand, there was no significant relationship between the risk of stroke recurrence and carrying the variant allele CYP2C19 *3 (P = 1.000). Ischemic stroke patients treated with clopidogrel and carrying a CYP2C19*2 allele had a higher risk of recurrent stroke as it is associated with reduced the metabolic activity of CYP2C19 enzyme leading to reduction of clopidogrel effect.